Elevated Hydrostatic Pressure Causes Retinal Degeneration Through Upregulating Lipocalin-2 - Yoneshige, Azusa; Hagiyama, Man; Takashima, Yasutoshi; Ueno, Satoru; Inoue, Takao; Kimura, Ryuichiro; Koriyama, Yoshiki; Ito, Akihiko (Frontiers in Cell and Developmental Biology, 2021)
Elevation of intraocular pressure is a major risk factor for glaucoma development, which causes the loss of retinal ganglion cells (RGCs). Lipocalin 2 (Lcn2) is upregulated in glaucomatous retinae; however, whether Lcn2 is directly involved in glaucoma is debated. In this study, retinal explant cultures were subjected to increased water pressure using a two-chamber culture device, and Lcn2 protein levels were examined by immunoblotting. In situ TdT-mediated dUTP nick and labeling (TUNEL) and glial fibrillary acidic protein (GFAP) immunohistochemical assays were performed to assess apoptosis and gliosis, respectively. The neurotoxicity of Lcn2 in the retinal explant culture was determined with exogenous administration of recombinant Lcn2. The Lcn2 protein levels, percentage of TUNEL-positive cells, and GFAP-positive area were significantly higher in retinae cultured under 50 cm H2O pressure loads compared to those cultured under 20 cm H2O. We found that Lcn2 exhibited neurotoxicity in retinae at dose of 1 µg/ml. The negative effects of increased hydrostatic pressure were attenuated by the iron chelator deferoxamine. This is the first report demonstrating the direct upregulation of Lcn2 by elevating hydrostatic pressure. Modulating Lcn2 and iron levels may be a promising therapeutic approach for retinal degeneration.